Creating community : the Jews of Springfield, Missouri - Ioannides, Mara W. Cohen (Greene County Historical Society Press, 2021)
"Creating community expands the written histories of Springfield that have long overlooked this minority in the local community. It also adds to the growing study of small Jewish communities around the United States. Springfield is both Southern and Midwestern in flavor and this is reflected in the Jewish community's development that has examples of both. Jews have been part of the economic development of the town since the 1860s. Since then, they have also been involved in fraternal and social organizations, politics, and education. This is not a complete history, but its purpose is not to be encyclopedic, rather it is to exemplify how this minority group were part of the growth of the Queen City of the Ozarks"--Back cover